OPTIMALISASI SEO DAN SEM UNTUK MENINGKATKAN PENJUALAN MELALUI WEBSITE E-COMERCE BERBASIS WORDPRESS-ELEMENTOR: Optimization of SEO and SEM to Increase Sales Through a WordPress-Elementor-Based E-Commerce Website - Abdul Hamid Arribathi; Dede Herman (Jurnal Investasi, 2026)
New era business actors are required to have effective and easily accessible promotional media, so an e-commerce website is needed. This research aims to design and develop a WordPress-based e-commerce website using Elementor as a page builder, as well as optimize it through the application of Search Engine Optimization (SEO) and Search Engine Marketing (SEM) to improve promotion and sales performance. The research methods and procedures include needs analize, website appearance and structure design, WooCommerce configuration, and implementation of on-page and off-page SEO strategies. The SEM stage is carried out through the creation of paid campaigns using Google Ads with a focus on keyword selection, ad copywriting, and performance monitoring through CTR, CPC, and conversion rate metrics. Website testing is conducted using PageSpeed Insight, GTMetrix, Google Analytics, and user evaluation to measure user experience (UX). The results of the study show that SEO optimization is able to increase website access speed, content relevance, and keyword ranking on search engines, so that organic traffic increases by more than 60%, thus increasing promotional reach and increasing CTR significantly, which has an impact on increasing the number of transactions. Meanwhile, the integration of WordPress Elementor-based website design and SEO and SEM optimisation has a positive impact on the effectiveness of promotional media and increased sales. These findings can be used as a reference in the development of digital marketing strategies for MSMEs and companies that want to increase competitiveness in the online market